AKTIVITAS SPESIFIK SELULASE Serratia marcescens DENGAN VARIASI KONSENTRASI AMONIUM SULFAT ((NH4)2SO4) DAN pH - Prawatya Cahyani; W Wijanarka; Budi Raharjo (Jurnal Akademika Biologi, 2017)
Cellulose is a component found in the cellular structure in almost all plant matter, its existence considered to be the most abundant on earth, and even excreted by some bacteria. Cellulose degradation is performed by cellulase enzymes consisting of three components, namely, endoglucanase, exoglucanase, and β-glucosidase enzyme with glucose as the final product. Cellulase utilization is often used in the textile, food and paper industries, whereas in the field of pharmaceuticals, cellulase enzymes are used to maintain optimal digestive health or produce substances that act as binding tablets such as methylcellulose, ethylcellulose, and hydroxypropylcellulose. The purpose of this study is to determine the concentration of ammonium sulfate and optimum pH for cellulose specific activity of Serratia marcescens. Determination of cellulase activity was done by DNS method, while determination of protein content was done by Lowry method. This research uses Randomized Block Design (RAK) factorial pattern with two factors. The first factor was variation of ammonium sulfate concentration which consisted of (0%, 0,75% and 1%). The second factor is the variation of pH consisting of 6, 7, and 8. Each factor is repeated 3 times. The data obtained were analyzed using Analysis Of Variance (ANOVA). The results showed that the combination of ammonium sulphate concentration variation with pH was not optimum to increase cellulose specific activity of S. marcescens.    Keywords: Cellulase, Ammonium sulfate, pH, Serratia marcescens